An analytical study of the relations between the relational scoring and maximum speed of the stages of study at the Faculty of Physical Education football - Naji , diaa (Journal of Physical Education, 2012)
The know Ledge of The Type of Relationship Between The high speed and kip the ball will hales the teachers to identify the term of the training course and good components according to his scientific information . the aims of research are *know the reaction of nigh speed and kip the boll in soccer.*know the reaction of the high speed and kite the ball in soccer.The subject of the study consist of (10)pupils in physical Education for university of Baghdad